Andrographolide attenuates complete freund's adjuvant induced arthritis via suppression of inflammatory mediators and pro-inflammatory cytokines. (28th October 2020) - Gupta, Swati; Mishra, K.P.; Kumar, Bhuvnesh; Singh, S.B.; Ganju, Lilly
Abstract: Ethnopharmacological relevance: Traditional plant-derived medicines have enabled the mankind in curing the wide spectrum of diseases throughout the ages. Andrographis paniculata (Burm.f.) Nees, is one of the traditional plant used as a folk medicine for the management of inflammation, arthritis, viral-bacterial infections and other ailments in India, China, Malaysia and other South-East Asian countries. Its major bioactive compound; andrographolide, a diterpenoid, also exerts cytoprotective properties and is reported to be effective in neuroprotection, hepatoprotection, etc. Aim: The study is aimed to explore the role of andrographolide in treatment of complete freund's adjuvant (CFA) induced arthritis. Materials and methods: The influx of immune cells, release of pro-inflammatory cytokines and subsequent accumulation of synovial fluid (swelling) and pain manifest into the disease. The present study used CFA induced Balb/c mice model and treated them intraperitoneally with andrographolide and dexamethasone (used as a positive control) on alternate days for six days. After 6 days, blood and peritoneal macrophages were collected to evaluate the expression of various arthritic markers and paw edema was measured on all days. Results: The in vitro and ex vivo experiments showed that andrographolide treated animal group had reduced paw edema, cell cytotoxicity and nitric oxide production than dexamethasone treated animal group. Further, the study revealed the mechanistic role of andrographolide in treatment of arthritis by suppressing battery of molecules like COX-2, NF-κB, p-p38, CD40, TNF-α, IL-1β and IL-6 involved in arthritis. Conclusion: The study showed the potent anti-arthritic effects of andrographolide and warrants further investigations on andrographolide for the development of safe and effective anti-arthritic drug. Graphical abstract: Image 1 Highlights: Pro-inflammatory cytokines and subsequent accumulation of synovial fluid in joints are prominent manifestation in arthritis. Andrographolide (Andro), a bioactive compound of plant Andrographis paniculata was used for the treatment of arthritis. In the adjuvant-induced arthritis mouse model, the effect of Andro and dexamethasone were compared. Histopathology, serology and cytology studies showed that andro can be a future remedy for the treatment of arthritis.